2017
DOI: 10.1016/j.artd.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Custom hemiarthroplasties for retention of existing hardware associated with osteogenesis imperfecta

Abstract: Osteogenesis imperfecta is a rare genetic disorder that presents with heterogeneous phenotypes ranging from brittle bones to impaired hearing. Because of the decreased bone mineral density frequently observed in this patient population, many patients experience recurring and long-term fractures, which often require orthopaedic management. With the advancement of nonsurgical and surgical management and increased longevity of patients with osteogenesis imperfecta, the incidence of osteoarthritis has risen, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The use of custom acetabular cups is applicable in the population with OI. Nishida et al abandoned THA and converted to a hemiarthroplasty during surgery because the acetabular anatomy was too small to seat a cup 10 . Custom-designed acetabular cups based on computed tomography have been shown to have superior accuracy in the setting of skeletal dysplasia, which presents with distorted acetabular anatomy 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of custom acetabular cups is applicable in the population with OI. Nishida et al abandoned THA and converted to a hemiarthroplasty during surgery because the acetabular anatomy was too small to seat a cup 10 . Custom-designed acetabular cups based on computed tomography have been shown to have superior accuracy in the setting of skeletal dysplasia, which presents with distorted acetabular anatomy 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided design and computer-aided manufacturing (CAD-CAM) components assist with the abnormal and distorted anatomy of patients with OI because standard components can be inadequate for some patients, especially in the setting of narrow canals and thin cortices 8 . Nishida et al demonstrated the use of custom implants in the setting of existing hardware 10 . The use of intraoperative fluoroscopy is an adjunct to aid the surgeon in the setting of a pseudocanal 12 .…”
Section: Discussionmentioning
confidence: 99%